The Ethnobotanical Study of Traditional Wedding Rituals among the Dayak Kanayatn Tribe - Candramila, Wolly; Hasanah, Siti Uswatun; Syamswisna, Syamswisna (Jurnal Ilmu Pertanian Indonesia, 2026)
The traditional wedding rituals of the Dayak Kanayatn use plants to reflect their spiritual bond with nature and contribute to biodiversity conservation through local knowledge. This study aimed to explore the variety of plant species utilized in traditional wedding rituals and interpret their cultural significance in supporting biodiversity conservation through culturally embedded practices in Dayak Kanayatn ceremonies in Ambawang Village, Kubu District, Kubu Raya Regency, West Kalimantan Province. The study took place from March to July 2023 across four hamlets—Tanah Kuning, Parit Sembilan, Kuala Ambawang, and Medan Sri. This ethnobotanical study employed methodological triangulation, incorporating interviews, observations and documentation. Informants were selected using the snowball sampling technique, beginning with key informants and continuing until data saturation was reached, indicated by the absence of new or relevant information. Traditional weddings begin with a series of rituals, including makan pulut tunang, makan pulut rakeh, ngelulus adat, pembagian pirikng panganten, and pituah. Thirteen plant species are used in three of the five wedding rituals. These plants are used symbolically, either as offerings to ancestral spirits or as ritual elements intended to summon them. The ritual use of these plants affirms their sacred role, stressing the need to conserve them as ecological and cultural assets in the future. Keywords: cultural-ecological aspect, Dayak Kanayatn, ethnobotany, plants utilization, traditional wedding